PERENCANAAN STRATEGIS PADA INDUSTRI FINANCIAL TECHNOLOGY STUDI KASUS : FINTECH ALAMI SHARIA - Suharmanto, Tri; Gustari, Irvandi; Zulkifli, Zulkifli (SEKOLAH PASCASARJANA PRESS, 2022)
This journal academics is a qualitative research by case study approach through descriptive analysis that focuses on startup business strategic planning in financial technology industry. The object of this research is PT. Alami Fintek Sharia (Alami Sharia) as financial technology P2P lending sharia licensed by Financial Service Authority (OJK). The research is based on some theories such as Porter's Generic Strategies, Competitive Profile Matrix, IFE-EFE Matrix (Internal Factor Evaluation dan External Factor Evaluation), IE Matrix, Grand Matrix Strategy, SWOT Analysis, QSPM and Balanced Scorecard. The use of such theories was intended for the company to be able to compete and possess sustainable competitive advantage